Assessment of Lipid Profile and Follistatin in Osteoarthritis - Samar Hasan Shammar (American Journal of Biomedicine and Pharmacy, 2025)
Osteoarthritis (OA) is a degenerative joint disease and a significant cause of disability worldwide. This study aimed to evaluate lipid profile abnormalities and serum follistatin levels in OA patients compared to healthy controls, elucidating their roles in disease pathogenesis. A case-control design included 50 OA patients and 50 age- and sex-matched controls. Lipid parameters, including total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), were analyzed alongside serum follistatin levels measured by enzyme-linked immunosorbent assay (ELISA). OA patients exhibited significantly higher TC, TG, and LDL-C levels and lower HDL-C levels than controls. Serum follistatin levels were also significantly elevated in OA patients and showed positive correlations with TC, TG, and LDL-C and a negative correlation with HDL-C. These findings highlight the interplay between lipid metabolism and inflammatory mediators in OA and suggest that lipid profile and follistatin levels may serve as potential biomarkers or therapeutic targets for the disease.